The Effect Ofhypnobirt Hing On The Intensity Of Pain In Childbirth Penuunan Kala 1 In Midwives Clinic Nining - Lili Yuliana Tambunan; Maidina Putri; Widya Surya Tri Pasa; Paramita Mustari; Sri Junita Simaremare (Sean Institute, 2023)
Discussion:Hypnobirthing is a technique that helps pregnant women get positive suggestions during pregnancy until before delivery so that pregnant women can undergo a smooth, safe and comfortable delivery process. One of the non-pharmacological methods that can be used to reduce labor pain is hypnobirthing. Objective: The purpose of this study was to determine the effect of hypnobirthing relaxation techniques to reduce pain in the first stage of midwifery clinic Nining. Method: this type of research is “Quasi experimental prepost test